2010
DOI: 10.1007/bf03395694
|View full text |Cite
|
Sign up to set email alerts
|

The Implicit Relational Assessment Procedure: Exploring the Impact of Private Versus Public Contexts and the Response Latency Criterion on Pro-White and Anti-Black Stereotyping Among White Irish Individuals

Abstract: The current research comprised two experiments that employed the Implicit

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
62
0
6

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 92 publications
(75 citation statements)
references
References 36 publications
4
62
0
6
Order By: Relevance
“…Similarly, Barnes-Holmes et al (2010b) reported that participants evaluated black and white non-security related civilians with a gun as 'Safe' whereas we might expect that they would be viewed as dangerous. Both these results could be explained as an artefact caused by a …”
Section: The Effect Of a Default Positive Framing Bias (H1)mentioning
confidence: 96%
See 2 more Smart Citations
“…Similarly, Barnes-Holmes et al (2010b) reported that participants evaluated black and white non-security related civilians with a gun as 'Safe' whereas we might expect that they would be viewed as dangerous. Both these results could be explained as an artefact caused by a …”
Section: The Effect Of a Default Positive Framing Bias (H1)mentioning
confidence: 96%
“…In another example, Barnes-Holmes, Murphy, Barnes-Holmes, and Stewart (2010b) found that participants associated pictures of a black person with a gun and pictures of a white person with a gun as 'Safe' (i.e., they were faster to press True rather than False to the joint presentation of a picture of a person with a gun and 'Safe'). This was not what the authors had predicted based on prior evidence that a civilian holding a gun in a neutral context would normally be considered as dangerous rather than safe (i.e., participants should FLAWS IN THE IRAP 8 press False quicker than True) 4 .…”
Section: Flaws In the Irapmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the earliest IRAP studies examined the response patterns of white participants toward pictures of black and white individuals (Barnes-Holmes, Murphy, et al, 2010).…”
mentioning
confidence: 99%
“…Since these experiments were reported, other studies have used the IRAP to assess beliefs and attitudes in a number of domains, including racial stereotypes (Barnes-Holmes, Murphy, et al, 2010;Drake et al, 2010;Rashid, Haas, & Timko, 2007), urban versus rural life (Barnes-Holmes, Waldron, Barnes-Holmes, & Stewart, 2009), sexual orientation (Cullen & Barnes-Holmes, 2008), and meat eating versus vegetarianism (Barnes-Holmes, Murtagh, . One study found that IRAP response latency predicted performance on measures of intelligence (O'Toole & Barnes-Holmes, 2009).…”
Section: Research Using the Irapmentioning
confidence: 99%